A fluorescence-based quantitative real-time PCR assay for accurate Pocillopora damicornis species identification - Thomas, L.; Stat, Michael; Evans, R.; Kennington, W. (Springer Verlag, 2016)
Pocillopora damicornis is one of the most extensively studied coral species globally, but high levels of phenotypic plasticity within the genus make species identification based on morphology alone unreliable. As a result, there is a compelling need to develop cheap and time-effective molecular techniques capable of accurately distinguishing P. damicornis from other congeneric species. Here, we develop a fluorescence-based quantitative real-time PCR (qPCR) assay to genotype a single nucleotide polymorphism that accurately distinguishes P. damicornis from other morphologically similar Pocillopora species. We trial the assay across colonies representing multiple Pocillopora species and then apply the assay to screen samples of Pocillopora spp. collected at regional scales along the coastline of Western Australia. This assay offers a cheap and time-effective alternative to Sanger sequencing and has broad applications including studies on gene flow, dispersal, recruitment and physiological thresholds of P. damicornis.